Development of Banking CSR Model for Community Empowerment Slum Area in Medan City - Saleh, Arifin; Dalimunthe, Ahmad Hidayah; Lubis, Faisal Hamzah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
Nowdays, there are 200.29 hectares of slum in Medan. The slum area is in 42 urban villages spread across 9 sub-districts. For the handling of slums in Medan, this is done through the Kotaku Program with funding for central and regional collaboration. Other parties that are expected to be involved in handling this slum area are the banks, in this case Bank Sumut, through their corporate social responsibility (CSR) funds. This is because Bank Sumut, which is a regionally owned company, has a commitment every year to channel CSR funds to all regencies / cities in Sumatera Utara. In 2015, Bank Sumut channeled CSR funds amounting to Rp. 13,746 billion. This study aims to find a new model of Bank Sumut CSR that is directed at empowering slum communities in the city of Medan. Research method with a qualitative approach. Data analysis by analyzing typological data. The output of this study is the Bank Sumut CSR model of community empowerment in slum areas in Medan City or scientific publications in national scientific journals and international journals. Bank Sumut's research results have a CSR Program that has been proven to help the community and its targets in the future should be directed to help empower the slum communities in the city of Medan. Bank Sumut's CSR model for the empowerment of slum communities in the city of Medan must reach infrastructure development, social assistance, and economic assistance with management involving Kotaku, the community, and non-governmental organizations.